Averrhoa bilimbi: A Prospective Source of Bioactive Compounds against Antimicrobial and Cytotoxic Activities - Abdul Mannan, Md.; Chandra, Liton; Nazmul Islam, A.B.M.; Saddam Hossain, Md.; Kudrat-E-Zahan, Md.; Kida, Tetsuya (Asian Journal of Chemistry, 2020)
Averrhoa bilimbi fruit has been studied to find out a possible source of bioactive compounds against antimicrobial and cytotoxic activity. To achieve this goal, total phenolic content and total flavonoid content, antioxidant, antimicrobial and cytotoxic activities of five different fractionates such as methanolic crude, petroleum ether, chloroform, ethyl acetate and water fraction of A. bilimbi were investigated by UV-vis spectrophotometry, disc diffusion and brine shrimp lethality test methods simultaneously. Other phytochemicals viz. carbohydrate, tannins, polyphenols, glycosides, etc. were also screened out by conventional test methods concurrently. Total phenolic contents and total flavonoid contents were found to be ranging from 3.807-262.129 mg GAE g–1 and 67.848-1159.061 mg CE g–1, respectively, in all the analyzed fractions. DPPH free radical scavenging activity revealed distinctive IC50 value of 5.63 and 10.26 μg mL–1 in the chloroform and ethyl acetate extractives. Fractionates of petroleum ether and methanolic crude also presented strong cytotoxic potential with the LD50 values of 8.89 and 20.3 μg mL–1 in the brine shrimp lethality bioassay test. Petroleum ether and ethyl acetate fractions exhibited good antimicrobial activity with the zone of inhibition against Bacillus cereus (11 mm and 14 mm) and Escherichia coli (7 mm and 9 mm). Finally, it has been recommended that A. bilmbi fruit might be an effective source of bioactive compounds against antimicrobial and cytotoxic activity as well as antioxidant with potent radical scavenging activity.